Cardiovascular risk factors in adolescence - Ramos,Elisabete (2007)
The present review will examine the relationships among behavioural and biological cardiovascular risk factors during adolescence and cardiovascular disease later in adult life. A consistent finding is the co-occurrence of behavioural cardiovascular risk factors such as smoking, alcohol consumption, unhealthy diets and physical inactivity. Although there are no consensual criteria to define adolescence overweight, it is the most prevalent cardiovascular risk factor representing an increasingly important health problem, and the increase in the prevalence overweight, among younger age groups, is likely to have effect on others biological cardiovascular risk factors during adolescence and long-term implications for cardiovascular disease. A cluster of risk factors that includes overweight, hypertension, dyslipidemia and insulin resistance was described in children and adolescents, leading to the hypothesis that the clustering process begins early in life and persists in adulthood.